Clues for biomimetics from natural composite materials - Lapidot, Shaul (2012)
Bio-inspired material systems are derived from different living organisms such as plants, arthropods, mammals and marine organisms. These biomaterial systems from nature are always present in the form of composites, with molecular-scale interactions optimized to direct functional features. With interest in replacing synthetic materials with natural materials due to biocompatibility, sustainability and green chemistry issues, it is important to understand the molecular structure and chemistry of the raw component materials to also learn from their natural engineering, interfaces and interactions leading to durable and highly functional material architectures. This review will focus on applications of biomaterials in single material forms, as well as biomimetic composites inspired by natural organizational features. Examples of different natural composite systems will be described, followed by implementation of the principles underlying their composite organization into artificial bio-inspired systems for materials with new functional features for future medicine.